2021
DOI: 10.15586/aei.v49i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy as an asthma comorbidity in children and adolescents: a practical approach through a real-world study

Abstract: Introduction: Several studies have shown interactions between food allergy (FA) and asthma, but the influence of FA in asthma traits has been scarcely studied. Methods: A real-world retrospective observational study was conducted among patients between 3 and 18 years old referred to our Asthma Clinic from November 2014 to November 2017. Data were obtained from daily clinical practice. Only patients properly diagnosed with asthma and FA were included. Results: 815 patients were included: 483 asthmatics and 332 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…We found higher blood EOS counts in patients with asthma or post-bronchodilator airflow limitation, consistent with previous evidence, which showed patients with COPD or asthma have increased EOS levels than those without [15,30]. This indicated that in patients with COPD or asthma, thresholds defining normal and high blood EOS counts could be different from the general population, even between males and females [31]. Based on data of European and American populations, the GOLD guideline has strongly recommended initiating ICS therapy when blood EOS count ≥300 cells/μL [13], which was shown useful to predict greater ICS effect on prevention of exacerbation [32].…”
Section: Discussionsupporting
confidence: 91%
“…We found higher blood EOS counts in patients with asthma or post-bronchodilator airflow limitation, consistent with previous evidence, which showed patients with COPD or asthma have increased EOS levels than those without [15,30]. This indicated that in patients with COPD or asthma, thresholds defining normal and high blood EOS counts could be different from the general population, even between males and females [31]. Based on data of European and American populations, the GOLD guideline has strongly recommended initiating ICS therapy when blood EOS count ≥300 cells/μL [13], which was shown useful to predict greater ICS effect on prevention of exacerbation [32].…”
Section: Discussionsupporting
confidence: 91%
“…A cross-sectional study of allergic diseases in 1154 college students aged 18–26 years showed that the comorbidity rate of 2 or more (≥2) allergic diseases was 7.9% [ 26 ]. Research has suggested that chronic sinusitis with nasal polyps (CRSwNP) [ 7 ] and FA also have a higher risk of multimorbidity with asthma [ 8 ]. This suggests that allergic multimorbidities are present in a consistent proportion of patients with allergic diseases, which warrants national awareness of their diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%
“…Although some birth cohort studies have been initiated to better understand this high incidence, the studies have almost exclusively targeted a single allergic entity [ 6 , 7 ]. A few prospective cohort studies have examined the multimorbidity of allergic diseases, but mostly in patients in early childhood [ 8 , 9 , 10 , 11 ]. Pols et al found that AR, allergic asthma, and AD have a 9.8 times higher risk of occurring simultaneously in children [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While specific and comprehensive data on the global prevalence of food allergies is limited, the World Allergy Organization (WAO) has estimated, based on data from 89 countries, that over 250 billion individuals throughout the globe are already affected by allergy diseases. This prevalence is expected to increase to 4 billion individuals by 2050 [ 200 , 201 , 202 , 203 ]. Food is a crucial source of health and nutrition, yet it is still a mystery why some food items can induce an allergic response in the body, which is the primary focus of research on food allergies.…”
Section: Allergenicity From Egg Proteinsmentioning
confidence: 99%